Role of Ninth Month Garbhini Paricharya as Partus Preparatory for easy and safe Delivery: A Critical Review - Thakur Jyotsna; Masand Sameet (AYUSHDHARA, 2022)
Pregnancy is women’s crowning creative experience of lifetime. Giving birth is an ecstatic, jubilant adventurous experience which brings a new life to the world. Pregnancy and labor have been an essential part of human existence for millennia but unfortunately the experience has not been so easy for all women. Every new mother aspires that end of this beautiful journey should be safe, smooth and comfortable with minimum pain, agony and aids. The well established Bishop’s score (BS) is most important criteria for assessment of cervix with a BS of 6 or less indicating an unfavorable cervix and a score of 8 or more a favorable one. On screening the Garbhini paricharya regimen specially month wise regimen mentioned in Ayurveda classics, it was found that, this regimen is highly scientific in terms of modern medical science for birth preparedness or to achieve Sukhprasava. From ninth month onwards, Acharya has mentioned to give Anuvasan basti i.e., medicated enema of oil medicated with Madhura skandha drugs along with Yoni Pichu (vaginal tamponing) of same oil. Therapies advised in the form of Anuvasana basti and Yoni pichu have potential of inducing effective cervical ripening (favorable Bishop’s score), efficient myometrial activation required for the onset of labour by virtue of its essential fatty acids, phytoestrogens and flavanoid content. So, it is high time to pave way towards Ayurveda and adopt holistic safe birth preparedness procedures for easy parturition and healthy obstetric outcome.